Beyond mass production : - Kenney, Martin (Oxford University Press, 1993)
This book explores the rise of this Japanese model and provides a detailed examination of the processes which have brought about its transfer to the United States. It presents new and original data on the extent of Japanese investment in both United States heavy industry and high technology and provides an empirically-grounded discussion of the reasons why this has occurred. The authors focus on the transfer of basic elements of Japanese production organization and develop a broad conceptual theme contrasting the Japanese model of production organization with that of United States Fordism. With a wealth of illustrations and straightforward examples, this work will appeal to those interested in urban and regional economics, industrial organization, labor relations, and economic geography.